2015
DOI: 10.1353/hpu.2015.0000
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Medicaid Participation among Florida Dentists

Abstract: Background Finding dentists who treat Medicaid-enrolled children is a struggle for many parents. The purpose of this study was to identify non-reimbursement factors that influence the decision by dentists about whether or not to participate in the Medicaid program in Florida. Methods Data from a mailed survey was analyzed using a logistic regression model to test the association of Medicaid participation with the Perceived Barriers and Social Responsibility variables. Results General and pediatric dentists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…This study also assessed whether certain characteristics of Medicaid‐enrolled dentists were associated with their level of participation in state Medicaid programs. Findings revealed that significant predictors of the level of clinical engagement are consistent with previous literature examining factors influencing Medicaid enrollment . These consistencies provide some external validity to this new method of measuring levels of Medicaid participation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study also assessed whether certain characteristics of Medicaid‐enrolled dentists were associated with their level of participation in state Medicaid programs. Findings revealed that significant predictors of the level of clinical engagement are consistent with previous literature examining factors influencing Medicaid enrollment . These consistencies provide some external validity to this new method of measuring levels of Medicaid participation.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings validate several demographic and practice characteristics of dentists [i.e., job status, self‐reported Medicaid participation, age, race, dental practice type ] as predictors of their participation in state Medicaid programs. Just as importantly, our study provides a novel method of measuring the relative contribution (clinical engagement) of dentists in state Medicaid programs by examining Medicaid claims counts and DHPSA designation resources in addition to state‐based licensure data.…”
Section: Resultssupporting
confidence: 74%
“…The study used the Deamonte Driver scenario survey, which measures factors affecting dentists’ participation in Medicaid 1 , 10 . The instrument, developed by Logan et al, did not report a factor structure in their study 1 . Therefore, for our study, the three‐factor solution reported by Behar‐Horenstein and Garvan was used 10 .…”
Section: Methodsmentioning
confidence: 99%
“…Failure to receive proper oral health care, including both prevention and maintenance, is influenced by myriad and complex social, economic, and dental factors, including access to care. Access to care is often dictated by patients’ or their family's ability to pay for the care or to afford dental insurance and is limited by the low participation of dentists in Medicaid, a federal‐state insurance program for low‐income individuals 1 . These barriers may lead to low utilization of dental services as well as limited knowledge about the relationship between oral and systemic health.…”
mentioning
confidence: 99%
“…While social justice is not explicitly mentioned, there is mention of core professional attributes such as altruism and social responsibility, both key issues with respect to treating underserved and diverse patients. Recent research reports cast unfavorable light on dentists’ attitudes towards these issues 42 46 . CODA standards related to altruism and social responsibility need further reinforcement in dental education in order to make progress in improving access and practice in increasingly diverse settings.…”
Section: Role Of Regulatory Agenciesmentioning
confidence: 99%